From the Greeks to the Arabs and Beyond : Volume 3: From God´s Wisdom to Science: A. Islamic Theology and Sufism, B. History of Science - Daiber, Hans (Islamic Philosophy, Theology and Science. Texts and Studies, 2021)
From the Greeks to the Arabs and Beyond written by Hans Daiber, is a six volume collection of Daiber's scattered writings, journal articles, essays and encyclopaedia entries on Greek-Syriac-Arabic translations, Islamic theology and Sufism, the history of science, Islam in Europe, manuscripts and the history of oriental studies. The collection contains published (since 1967) and unpublished works in English, German, Arabic, Persian and Turkish, including editions of Arabic and Syriac texts. The publication mirrors the intercultural character of Islamic thought and sheds new light on many aspects ranging from the Greek pre-Socratics to the Malaysian philosopher Naquib al-Attas. A main concern is the interpretation of texts in print or in manuscripts, culminating in two catalogues (Vol. V and VI), which contain descriptions of newly discovered, mainly Arabic, manuscripts in all fields. Vol. I: Graeco-Syriaca and Arabica. Vol. II: Islamic Philosophy. Vol. III: From God's Wisdom to Science : A. Islamic Theology and Sufism ; B. History of Science. Vol. IV: Islam, Europe and Beyond: A. Islam and Middle Ages ; B. Manuscripts - a Basis of Knowledge and Science ; C. History of the Discipline ; D. Obituaries ; E. Indexes. Vol. V: Unknown Arabic Manuscripts from Eight Centuries - Including one Hebrew and Two Ethiopian Manuscripts: Daiber Collection III. Vol. VI: Arabic, Syriac, Persian and Latin Manuscripts on Philosophy, Theology, Science and Literature. Films and Offprints: Daiber Collection IV.